Pengembangan Website Manajemen Jasa Laundry Berbasis PHP Native Untuk Meningkatkan Efisiensi Pelayanan - Widiasih, Komang Sri; Apsari, Ni Putu Yulinda; Artanti, Putu Dian Apti; Sanjaya, I Gede Wahyu (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
The continuous advancement of information technology is driving businesses to continually improve the quality of their services, including in the laundry service industry. Fresh Clean Laundry still faces several challenges in its manual data management processes, such as difficulties in recording transactions, searching for customer data, managing payments, and generating reports. This study aims to develop a PHP Native-based laundry service management website that can help improve service effectiveness and efficiency. The system development method used is the Waterfall model of the Software Development Life Cycle (SDLC), which consists of the requirements analysis, system design, development, testing, and maintenance stages. The system was built using the PHP Native programming language. System testing employed the Black Box Testing method across 5 modules with 12 scenarios. Based on the test results, all features achieved a valid status with a 100% success rate, indicating that the system is ready for use. The research findings indicate that the developed website is capable of supporting the integrated management of customer data, laundry transactions, payments, and services. System testing conducted on each key feature shows that all functions are operating in accordance with the specified requirements. With this system in place, data management processes have become faster, more accurate, and better organized, thereby improving the quality of service at Fresh Clean Laundry.